Changes in the masticatory organ in patients with Recklinghausen’s disease – a case report - Kopczyński, Przemysław; Flieger, Rafał; Matthews-Brzozowska, Teresa (Contemporary Oncology/Współczesna Onkologia, 2012)
In the report the authors present changes in the masticatory organ in the case of a 9-year-old girl affected with Recklinghausen’s disease. The characteristics included neurofibromatosis of the face, salivary gland and external ear in the form of an extensive tumour. The disease also resulted in acute right hemifacial hypertrophy. The computer-assisted tomography examination identified acute atrophy of the zygomatic bone, maxilla, mandible alveolar ridge and right base of the skull. The clinical intraoral examination of the patient revealed right buccal occlusion and lingual occlusion on the opposite side. The patient underwent functional orthodontic treatment of the co-existing malocclusion with an orthodontic appliance for the upper and lower jaw which was to prevent further mandible movement towards the right. According to researchers, neoplasia is an inherent characteristic of a phenotype seen in patients suffering from Recklinghausen’s disease. Therefore, it is the main factor influencing the selection of a therapy. Although there are certain single attempts of pharmacological treatment of ganglioneurofibromas at their early development stage, it is agreed that, in fact, no preventive actions are possible. Hence, in the case of neurofibromatosis type 1, reconstruction and aesthetic procedures are widely applied in treating the disease.